Corporate Mobility and Company Law. Issue 5 (September 2016) - Ferran, Eilís
Abstract : Globalisation has given commercial parties more freedom to choose the company law system that best suits their private needs. The growing range of techniques to facilitate choice between systems of company law reshapes the mandatory/enabling debate in countries where corporate mobility is a relatively new business phenomenon and where the past focus has mostly been on degrees of flexibility within domestic law. This article examines relocations, both out of and into the UK, as a source of learning on market preferences with respect to company law and on vulnerabilities. It considers the wider policy implications for the development of company law of more freedom of choice between company law systems. It concludes with a call to explore the potential for more optionality within company law to counter the rise of choice between systems of company law.